2022
DOI: 10.1002/jvc2.36
|View full text |Cite
|
Sign up to set email alerts
|

Associations among bullous pemphigoid and various neurological diseases: A systematic review and meta‐analysis

Abstract: Bullous pemphigoid is a common autoimmune bullous skin disease of the elderly. The objective of this meta-analysis was to assess the association of bullous pemphigoid with neurological disease. We conducted a systematic search of three databases, screening for articles with relevant search terms from database inception until August 01, 2020. The Newcastle-Ottawa quality assessment scale was used to evaluate the quality of the retained articles.Random effects models were applied to calculate the pooled odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Similarly, in a study including a larger sample of BP patients, Khosravani et al reported no difference between BP patients and controls in terms of MS. Nevertheless, MS has been linked to BP in multiple studies 16,18,22,24 . On the other hand, the risk of Parkinson's disease appears to be higher in BP patients, 22 yet we were not able to evaluate its pattern in our study.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Similarly, in a study including a larger sample of BP patients, Khosravani et al reported no difference between BP patients and controls in terms of MS. Nevertheless, MS has been linked to BP in multiple studies 16,18,22,24 . On the other hand, the risk of Parkinson's disease appears to be higher in BP patients, 22 yet we were not able to evaluate its pattern in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, MS has been linked to BP in multiple studies 16,18,22,24 . On the other hand, the risk of Parkinson's disease appears to be higher in BP patients, 22 yet we were not able to evaluate its pattern in our study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The relationship between BP and cognitive outcomes is not well understood and may involve multiple factors. Some possible mechanisms include the direct effect of autoantibodies on the central nervous system (CNS), the systemic inflammation induced by BP, the shared genetic susceptibility or environmental triggers between BP and neurological disorders, and the confounding effect of age or other comorbidities [ 15 , 16 ]. Therefore, it is important to confirm the association between BP and cognitive outcomes using rigorous methods and large samples, and to explore the potential mediators and moderators of this relationship.…”
Section: Introductionmentioning
confidence: 99%